Measurement of beauty production from dimuon events at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Bellagamba, L; Boscherini, D; et al. (2009)
Beauty production in events containing two muons in the final state has been measured with the ZEUS detector at HERA using an integrated luminosity of 114 pb-1. A low transverse-momentum threshold for muon identification, in combination with the large rapidity coverage of the ZEUS muon system, gives access to almost the full phase space for beauty production. The total cross section for beauty production in ep collisions at (s)1/2 = 318 GeV has been measured to be σtot(ep bX) = 13.9 1.5(stat.)+4.0-4.3(syst.)nb. Differential cross sections and a measurement of b correlations are also obtained, and compared to other beauty cross-section measurements, Monte Carlo models and next-to-leading-order QCD predictions. © 2009 SISSA.